Characterization of bbtTICAM from amphioxus suggests the emergence of a MyD88-independent pathway in basal chordates - Yang, Manyi (Nature Publishing Group, 2011)
The MyD88-independent pathway, one of the two crucial TLR signaling routes, is thought to be a vertebrate innovation. However, a novel Toll/interleukin-1 receptor (TIR) adaptor, designated bbtTICAM, which was identified in the basal chordate amphioxus, links this pathway to invertebrates. The protein architecture of bbtTICAM is similar to that of vertebrate TICAM1 (TIR-containing adaptor molecule-1, also known as TRIF), while phylogenetic analysis based on the TIR domain indicated that bbtTICAM is the oldest ortholog of vertebrate TICAM1 and TICAM2 (TIR-containing adaptor molecule-2, also known as TRAM). Similar to human TICAM1, bbtTICAM activates NF-κB in a MyD88-independent manner by interacting with receptor interacting protein (RIP) via its RHIM motif. Such activation requires bbtTICAM to form homodimers in endosomes, and it may be negatively regulated by amphioxus SARM (sterile α and armadillo motif-containing protein) and TRAF2. However, bbtTICAM did not induce the production of type I interferon. Thus, our study not only presents the ancestral features of vertebrate TICAM1 and TICAM2, but also reveals the evolutionary origin of the MyD88-independent pathway from basal chordates, which will aid in understanding the development of the vertebrate TLR network.